Gambaran Perilaku Masyarakat Terhadap Penanganan Luka Bakar Di Rumah - M. Agung Akbar; Fitriani Agustina (Jurnal Kesehatan Komunitas, 2023)
Handling burns quickly and appropriately will not cause adverse effects on the body. First aid is the initial treatment for the acute phase, which aims to improve the healing process, prevent injury severity, reduce pain, and save lives. The purpose of this study was to determine the description of community behavior toward the treatment of burns. This study uses a quantitative approach with a descriptive design. This research was conducted in the working area of the Puskesmas in Ogan Komering Ulu Regency in December 2021 by distributing online questionnaires using a google form. Sampling using a simple random sampling technique as many as 113 people using the Slovin formula. The description of the behavior of the community in the working area of the Puskesmas in Ogan Komering Ulu Regency towards the treatment of burns at home shows that 113 respondents showed poor behavior (59.29%). The usual procedure for treating minor burns at home is using toothpaste (64%) and ice (25%). The conclusion is that there is a fact that first-aid burns show poor behavior. The results of the study require health education from primary health services who are responsible for explaining the problem and initiating health education.